A concepção de infância nas orientações curriculares para a Educação Infantil: um estudo sobre o documento da Prefeitura de São Paulo no período de 2005-2012 - Mota, Georgina Lopes da (2017)
This thesis originates from a research to investigate which conception of childhood was implicit in the curricular proposal for early childhood education in the curricular guidelines, expectations of learning, and teaching guidelines for early childhood education in the period from 2005 to 2012 in the city of São Paulo. Studies on childhood have guided different discussions on the visibility of the child in early childhood programs. The child is recognized as a subject of rights by the Federal Constitution and childhood, as the first stage of basic education by the law of Guidelines and Bases of education, which was reflected in the construction of political measures in municipalities for fitness to new definitions of legal norms. The Municipal Secretary of education of the city of São Paulo, by taking the formal education of children from zero to three years, implemented new educational policies to the adequacy of the education and care of children in the age group of zero to six years. To investigate that period of early childhood education in Department of education policy, this research utilized a qualitative method of analysis of documents. The chosen document was the last document produced by the Municipal Secretary of Education with curricular orientation at the beginning of the studies. The first chapter sought to construct the theoretical foundations, rescuing the history of childhood, the contribution of the sociology of childhood and socio-historical psychology. The second chapter described the history of early childhood education and curriculum, emphasizing the history of education in Brazil and in São Paulo. To parse the document, the analysis methodology used was the hermeneutics of depth by J. Thompson. For the formal approach, we opted for the content analysis technique, which resulted in issues of significance for the interpretation of the data. In this sense, we can say that the conception of childhood, in social perspective and historically constructed, is considered a social category. In relation to the practice, the child should be the Center and the curriculum should articulate her knowledge with new knowledge. From this finding, this study concluded that the curricular guidelines for early childhood education, to define the learning expectations in pedagogical practice, restricted the autonomy of the teacher in the selection of learning, and conceived the childhood as a period of development and learning, focusing on the preparation for the later stage